(3QSGdI aj GdehGYXs - (3eLghds ((3YKeGf Hf GdaGge YHO GdQMefs)
(3ChdgG (B:s
(3agPG fbd eeG jcJH ddMOjK GdCeKGd (B((3cPG(B) (3dCf GddgJYGdi Ndb cd TjA GKfjf EdG gh hMOg aEfg dG Edg EdG gh Ndb GdSehGJ hGdCQVs
(3BNQgG (B:s
(3dG jYde YOO YdGeGJ GdfaGb EdG Gddg hdPdc GNJUQJ aj PcQg, bGd Gddg JYGdi (B{(3hjYPH GdefGabjf hGdefGabGJ hGdeTQcjf hGdeTQcGJ(B} (3GdBjIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs